Peculiarities in blood supply to the thigh region as the morphological basis of a tactics for the surgical treatment of fractures - Zhуlyayev, Ruslan; Tyazhelov, Olexiy; Zaritsky, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article describes practical recommendations for doctors of the surgical field; they were developed on the basis of morphological and experimental methods of investigation of the variant topography of the femoral arterial bed.